The Effect of Investment, Local Own Revenue, and Employment on Economic Growth (Case Study in East Java 200-2014) - Ramadhanty, Deby Reynanita (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
Economic growth is one indicator that is very important in the analysis of the economic development that occurs in a country. Economic growth showed the extent to which economic activity will resulting additional income of the people in a given period. Economic growth can also be interpreted as a process that the changes can be felt in the long term and it can be measured from the increase in total output so that resulting in increased prosperity of society. This research aims to analyze the effect of investment, local own revenue, and labor on economic growth in East Java in 2000-2014.This research uses multiple linear regression method used to determine the effect of independent variables on the dependent variable. The results obtained in this research indicate that investment variable do not affect economic growth, meanwhile the variable of local own revenue has a positive and significant effect on economic growth and labor has no significant effect on economic growth in East Java.Keywords: Economic growth, investment, local own revenue, employment